Implementation of Mind Mapping to Improve English Learning Achievement of the First Semester Students of Elementary Teacher Education Department of IAIN Takengon - Kardi, Sungkawati (Malewa: Journal of Multidisciplinary Educational Research, 2023)
Applying mind mapping helps students attain their target learning. This descriptive qualitative research study aims to describe the implementation of mind mapping method to improve English learning achievement of the semester 3 students of Elementary Teacher Education Department of IAIN Takengon. The respondent of this research were 28 students. The data were analyzed descriptively. The result of this study are as follow. Mind mapping method is one of the learning methods that helps students understand the material given by the teacher because this method explains a material in detail and only conveys important points, also opens ideas or ideas that are difficult to issue in study.